A Halophila baillonis Ascherson bed on the semiarid coast of Brazil. Issue 3 (July 2014) - Barros, Kcrishna; Costa, Francimeire; Rocha‐Barreira, Cristina
Abstract: The present study records Halophila baillonis and describes the specimens of the Environmental Protection Area of the Parnaíba River Delta, Piauí, semiarid coast of Brazil. In August 2014, we mapped and characterized the seagrass meadow, and georeferenced the extent of H. baillonis patches within the area. Ten ramets were collected manually for biometric measurements, and five samples were collected using a PVC corer of 10 cm in diameter, inserted at 15 cm depth, to obtain averages of shoot density and belowground/aboveground biomass ratios. Apart from H. baillonis, we recorded Halodule wrightii, Halodule sp. and Halophila decipiens, characterizing the seagrass meadow of Cajueiro da Praia as the most diverse on the Brazilian coast. Average density was between 96 and 1401 shoots m –2 ; total biomass ranged from 14.3 g dw m –2 to 27.1 g dw m –2 ; and leaf size 7.8 to 23.8 mm. In general, density, biometric and biomass values of the plants were greater than or at the upper range described in other areas, co‐occurring with other seagrass species and on a variety of sediments, indicating a well‐established bed. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)